Practices of pregnant women regarding tobacco and alcohol use during pregnancy at one primary health care clinic in Southern Namibia - Selma Hamutenya; Emma M. Nghitanwa (AOSIS, 2023)
Tobacco and alcohol use during pregnancy has negative consequences for the fetus. The study's purpose was to investigate the practices of pregnant women regarding the use of tobacco and alcohol during pregnancy. A quantita‑ tive research approach with a descriptive, cross‑sectional, analytical design was used. The population was all pregnant women aged 18 years and above attending antenatal care at the Mariental clinic. Written informed consent was obtained from all respondents prior to data collection. Data was collected from 211 respondents selected through a systematic sampling. Data was analyzed using Statistical Package of the Social Sciences version 27. Descriptive statistics were used for frequencies and percentages. Fisher's Exact test at 0.05 alpha level was used to determine the association between variables. The mean age was 28.8, with a standard deviation of 6.9 years. Most participants, 92 (43.6%), were aged between 18 and 24 years. The majority, 186 (88.15%), were in the third trimester of pregnancy, and 154 (73%) were single. Most, 148 (70.14%), respondents have good practices towards alcohol use during pregnancy. Moreover, 190(90 %) of the respondents were classified as having good practices towards tobacco use in pregnancy. Educational levels showed a significant association with practices towards tobacco smoking (P=0.042). The study concluded good practices among pregnant women on alcohol and tobacco smoking during pregnancy. It is recommended that health facilities should introduce awareness campaigns on the dangers of alcohol and tobacco use during pregnancy. Moreover, educational materials should be developed in local languages and distributed to the community.